Endoscopic submucosal dissection for sessile, nonampullary duodenal adenomas - Jung, J. H.; Choi, K. D.; Ahn, J. Y.; Lee, J. H.; Jung, H.-Y.; Choi, K.-S.; Lee, G. H.; Song, H. J.; Kim, D. H.; Kim, M.-Y.; Bae, S. E.; Kim, J.-H. (Endoscopy, 2013)
Although endoscopic submucosal dissection (ESD) is increasingly utilized to treat early neoplasms of the gastrointestinal tract, its use for duodenal neoplasms is limited by the thin wall and narrow lumen of the duodenum. We have reviewed cases where ESD was used to treat sessile, nonampullary duodenal neoplasms. To do this, we retrospectively reviewed the medical records of patients treated with ESD for adenomas of the duodenum from January 2001 to December 2010, assessing the curative outcomes and complication rates. A total of 14 cases were reviewed. Mean patient age was 56.4 years. The mean size of tumors and mean size of the specimens were 17.1 mm and 26.4 mm, respectively. The en bloc resection rate with ESD was 78.6 %, and the complete (R0) resection rate was 85.7 %. No patient in the study experienced major bleeding. However, second-look endoscopy revealed minor bleeding requiring endoscopic homeostasis in one case (7.1 %). Perforations were observed in five cases (35.7 %). Two of the five patients with perforation underwent surgery. The ESD methods yielded acceptable curative resection rates for duodenal adenomas, although ESD was associated with a higher rate of perforation. Therefore, duodenal ESD should be performed with care and only in selected patients to avoid serious complications.